The Relationship between Women's Peer and Social Networking Site Thinness Discrepancies and Body Dissatisfaction. Issue 5 (19th October 2020) - Flynn, Mark A.; Lin, Linda; Champigny, Lauren
ABSTRACT: We explored the link between adult women's peer and social networking site (SNS) thinness discrepancies on body satisfaction. We assessed discrepancies between women's perceived actual thinness and the thinness ideal of close female and male peers, and the female thinness ideal of women and men on social networking sites (SNSs). A total of 253 women ( M age  = 37; SD  = 11.41) completed a cross-sectional survey online. Discrepancies from SNS groups were significantly greater than peer groups. Also, all discrepancies were linked to body dissatisfaction. Finally, the discrepancy with SNS women was the most significant predictor of body dissatisfaction. Our findings also expand the use of self-discrepancy theory by examining SNS-specific discrepancies and do so alongside peer discrepancies to assess their relative effects on body satisfaction.